Exploring the Ecotourism Potential of Tapalinna and Bujung Manurung Villages: Balancing Nature, Culture, and Sustainability - Setiawan, Puguh Andhi; Wiweka, Kadek; Parantika, Asep (Sekolah Tinggi Pariwisata AMPTA Yogyakarta, 2024)
The village ecotourism planning in Tapalinna and Bujung Manurung Villages, Mambi Sub-district, Mamasa District, West Sulawesi Province was conducted to identify natural and cultural resources, as well as assess community readiness for managing these resources. The methods used included observation, the distribution of questionnaires to 30 respondents from the community, visitors, and managers, as well as the design of tourism programs and promotional media. The findings reveal that Tapalinna and Bujung Manurung Villages possess various cultural tourism potentials, including the Mambi language, religious systems, kinship systems, and local arts. Additionally, the villages have diverse natural tourism resources, such as flora and fauna. The community and managers showed positive perceptions and readiness toward the ecotourism planning, with a high level of preparedness. The designed tourism programs include daily, overnight, and annual tours, supported by promotional media in the form of posters themed